Pragmatics in conversation: a hallmark for diversity / A. Kamisah ... [et al.] - A., Kamisah; A., Norazlan; R., Azlini; M., Raihanah (2002)
This paper is about conversation. In specific, it is about what happens when people talk to one another. Our main focus is what may happen when two or more people exchange words for some reasons. Why does one person say one thing and the other reply as he or she does? In conversation, diversity is the hallmark. There is a wide range of alternatives to choose from when we want to say something. However, these alternatives, may sometimes lead to problems in communication. We usually do not realize that what we intend to say is not exactly perceived by the people we talk to. Many instances of rudeness, stubbornness, inconsiderateness, or refusal to cooperate (which are not the original intention of the speaker) are actually the results of the hearer's failure to grasp the pragmatics of the speech uttered. This paper looks at the failure of interpreting pragmatics in conversation and the problems that may arise from it.